Serendipitous nebular-phase JWST imaging of SN Ia SN 2021aefx: testing the confinement of 56Co decay energy - Mayker Chen, Ness; Tucker, Michael A.; Hoyer, Nils; Jha, Saurabh W.; Kwok, Lindsey A.; Leroy, Adam K.; Rosolowsky, Erik; Ashall, Chris; Anand, Gagandeep; Bigiel, Frank; Boquien, Médéric; Burns, Chris; et al. (The astrophysical journal. Part 2, Letters, 2023)
We present new 0.3-21 μm photometry of SN 2021aefx in the spiral galaxy NGC 1566 at +357 days after B-band maximum, including the first detection of any Type Ia supernova (SN Ia) at >15 μm. These observations follow earlier JWST observations of SN 2021aefx at +255 days after the time of maximum brightness, allowing us to probe the temporal evolution of the emission properties. We measure the fraction of flux emerging at different wavelengths and its temporal evolution. Additionally, the integrated 0.3-14 μm decay rate of Δm 0.3-14 = 1.35 ± 0.05 mag/100 days is higher than the decline rate from the radioactive decay of 56Co of ∼1.2 mag/100 days. The most plausible explanation for this discrepancy is that flux is shifting to >14 μm, and future JWST observations of SNe Ia will be able to directly test this hypothesis. However, models predicting nonradiative energy loss cannot be excluded with the present data.
Gesehen am 06.04.2023